2011
DOI: 10.1128/jb.01293-10
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Three Erwinia amylovora Phages Isolated in North America and a Bacteriophage Induced from an Erwinia tasmaniensis Strain

Abstract: Fire blight, a plant disease of economic importance caused by Erwinia amylovora, may be controlled by the application of bacteriophages. Here, we provide the complete genome sequences and the annotation of three E. amylovora-specific phages isolated in North America and genomic information about a bacteriophage induced by mitomycin C treatment of an Erwinia tasmaniensis strain that is antagonistic for E. amylovora. The American phages resemble two already-described viral genomes, whereas the E. tasmaniensis ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…carotovora (14,18) or other Erwinia spp. have been isolated (4,11,12), and a few of these species have been sequenced. Although we have announced the complete sequence of P. carotovorum subsp.…”
mentioning
confidence: 99%
“…carotovora (14,18) or other Erwinia spp. have been isolated (4,11,12), and a few of these species have been sequenced. Although we have announced the complete sequence of P. carotovorum subsp.…”
mentioning
confidence: 99%
“…At present, control of E. amylovora with bacteriophages is under investigation mainly in Canada and in the United States of America. Studies in Europe are currently limited to only a few countries with a primary focus on the morphology, molecular characterization, and host range studies of E. amylovora phages and examination of phage efficacy during in vitro conditions [61,67,[74][75][76][77]. Apart from some exceptions, these investigations do not report any field experiments with these phages.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Based on their PCR analysis results using primers specific for American phages, they found that the phages from Germany isolated by Müller and co-workers seem to be different from the North American bacteriophages. Müller et al [77] described the genome sequence of three E. amylovora phages from North America (ФEa1h, ФEa100, ФEa104), and a novel phage, ФEt88, that was isolated as a prophage of E. tasmaniensis Geider et al, an antagonistic bacterium for E. amylovora from Australia (nucleotide sequences are available in the EMBL database under accession numbers FQ482084, FQ482086, FQ482083 and FQ482085).…”
Section: Molecular Characterization Of Phagesmentioning
confidence: 99%
“…carotovorum-targeting phage PP1 consisted of a length of 44,400 bp with a GC content of 49.74%, encoding 48 ORFs with no tRNA. Although six phage genomes are available in the GenBank database infecting Erwinia amylovora, E. tasmaniensis, and E. pyrifoliae to date (6,8), there is no report on the complete genome sequence of the P. carotovorum subsp. carotovorum-infecting phage.…”
mentioning
confidence: 99%